2004
DOI: 10.1128/mcb.24.5.2041-2051.2004
|View full text |Cite
|
Sign up to set email alerts
|

A Microdomain Formed by the Extracellular Ends of the Transmembrane Domains Promotes Activation of the G Protein-Coupled α-Factor Receptor

Abstract: The ␣-factor receptor (Ste2p) that promotes mating in Saccharomyces cerevisiae is similar to other G protein-coupled receptors (GPCRs) in that it contains seven transmembrane domains. Previous studies suggested that the extracellular ends of the transmembrane domains are important for Ste2p function, so a systematic scanning mutagenesis was carried out in which 46 residues near the ends of transmembrane domains 1, 2, 3, 4, and 7 were replaced with cysteine. These mutants complement mutations constructed previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
50
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 59 publications
9
50
0
Order By: Relevance
“…The drop in reactivity is thought to correspond to the membrane interface region of the TMDs. Although a number of different factors can influence the reactivity of any one particular residue in STE2, a drop in reactivity over 3-5 residues is consistent with expectations for an α-helical TMD that is crossing the membrane boundary zone (14). Similar results were observed for the solvent accessibility of Cys-substituted residues in rhodopsin (28)(29)(30)(31), and the results were subsequently found to correlate well with the TMD arrangement observed in the rhodopsin crystal structure (27).…”
Section: Ste2 Topologysupporting
confidence: 81%
See 2 more Smart Citations
“…The drop in reactivity is thought to correspond to the membrane interface region of the TMDs. Although a number of different factors can influence the reactivity of any one particular residue in STE2, a drop in reactivity over 3-5 residues is consistent with expectations for an α-helical TMD that is crossing the membrane boundary zone (14). Similar results were observed for the solvent accessibility of Cys-substituted residues in rhodopsin (28)(29)(30)(31), and the results were subsequently found to correlate well with the TMD arrangement observed in the rhodopsin crystal structure (27).…”
Section: Ste2 Topologysupporting
confidence: 81%
“…The degree of biotinylation was then determined by quantitative Western blot analysis using anti-HA antibody to detect total STE2, and Streptavidin to detect biotinylated STE2 as described below. This procedure is a modification of the method used previously to analyze the reactivity with MTSEA-biotin of residues in the extracellular regions of STE2 (14). Previously, Streptavidin beads were used to precipitate the biotinylated STE2 proteins, whereas the new approach uses anti-HA beads.…”
Section: Mtsea-biotin Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Induced conformational changes in the ECL2 have been documented in several GPCRs, including the D2 dopamine receptor and C5A complement receptor (44,45) upon ligand occupancy of the orthosteric pocket in the TM domain. Long range conformational changes associated with ligand binding have been shown in ECL1 of glucagon receptor (46); the N terminus, ECL1, and extracellular ends of all TM helices of Saccharomyces cerevisiae G protein-coupled receptor Ste2p are known (47)(48)(49). These observations suggest that a mutation in a particular domain of the receptor causes a local structural perturbation that is eventually transmitted to other domains, leading to a global consequence in terms of affinity toward ligands and G protein.…”
Section: Ecl2 Conformation In Activation State Mutants Of At1rmentioning
confidence: 89%
“…These studies together with extensive molecular biology investigations (19)(20)(21)(22)(23) have indicated likely interactions between Y266 and residues near the amine terminus of α-factor. Very recently, biochemical evidence based on disulfide crosslinking indicated that N205 and Y266 might be close in an activated state of Ste2p as represented by a constitutively active mutant of this GPCR (24).…”
mentioning
confidence: 99%